TELAAH LITERATUR PELEPASAN INFORMASI MEDIS DAN PENGKLAIMAN BIAYA PELAYANAN PASIEN COVID-19 DI RUMAH SAKIT - Sali Setiatin; Yuwanita Kartikaningrum (POLITEKNIK PIKSI GANESHA, 2021)
ABSTRACT This topic was choosen aimed to literature review medical information release and claims Covid-19 patient care costs in hospitasl. Type of review used with literature review methods. Data source used is a secondary data source obtained through Google and Google Scholar, choosed by inclusion criteria. The literature review is based on two journals about releasing medical information for patient financing. The results of the literature review in the two journals, there are similarities in the application of the procedure for the release of medical information, namely that there are still inconsistencies in: 1) The third party applicant does not include a power of attorney and incomplete filling of medical records, especially the medical resume form 2) The officer is not careful to re-examine the completeness filling out requests for medical information so that it can affect the confidentiality of medical records. Recommendations given include: 1) Further researchers can use a qualitative method with a descriptive approach, using triagulation data collection techniques between observation, interviews, and documentation that the information required is in accordance with the research 2) For further researchers, they must use indicators for the release of medical information, namely procedures for requesting medical information, requesting parties, medical information makers, forms, and delivery of medical information that the release of medical information can be known in accordance with the provisions as evaluation.